The way home : a princess story - Lucado, Max.; Elwell, Tristen (Nashville, Tenn. : T. Nelson, 2005)
A beloved princess, adopted years ago as a foundling, longs to travel beyond the castle walls where the Lowlanders are said to play all the day long.
2.9
K-3
Keywords: Princesses -- Juvenile fiction; Kings and rulers -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Princesses -- Fiction; Kings, queens, rulers, etc. -- Fiction; Fathers and daughters -- Fiction; Princesses -- Fiction; Kings and rulers -- Fiction; Father-daughter relationship -- Fiction